A SMOKING BAN THAT TRESPASSES (Tufts Archival Research Center, 2007)
Editorial from Colorado Springs Gazette-Telegraph (2/10/94) against proposed federal workplace smoking ban, the Smoke-Free Environment Act. Argues that ban violates property rights. Claims that this is not a health issue, but rather an issue of government intrusion of private property and violation of free-market principals under the ruse of public health. Supports private business owners who have made decision to ban smoking independently.